Community-based assessment for infant, under-5 child and maternal mortality in tribal population of Himachal Pradesh, India - Ashok Bhardwaj; Mitasha Singh; Sanjay Kumar; Piyush Sharma (College of Community Physicians of Sri Lanka, 2023)
Introduction: Infant and child mortality rates are sensitive indicators of health services of any community. Tribal populations remain a disadvantaged group among other communities and the indicator of their accessibility and availability of health services is the infant and maternal mortality rates. Objectives: To assess reliable estimates and causes for the child (less than five year of age) mortality rate and maternal mortality ratio (MMR) of tribal population of Himachal Pradesh, and the maternal and child health services and facilities available in their health institutions Methods: A community-based surveillance study was conducted in 2019-20 on the deaths of all children (less than five year of age) and maternal deaths in the entire population of two tribal districts i.e., Kinnaur and Lahau l & Spiti, and of two tribal blocks of Chamba District in the state of Himachal Pradesh. Sub-centres (SC) remained under the study for a period of one year. Verbal autopsies were conducted to ascertain the cause of death by community workers under the supervision of project staff. In addition, a cross-sectional facility survey was conducted, Health institution data were gathered using a pre-tested structured schedule adapted from the National Health Mission Facility Assessment Tool. Results: Majority (85%) of the SCs were functioning in Kinnaur District and 66% at Lahaul & Spiti District. In the latter district, the labour room was functional at primary health center (PHC). Civil and district hospitals were preferred for delivery while SC and PHC were preferred for preventive services. The infant mortality rate (IMR) of all districts was 24 per 1000 live births (LB). Most of the deaths were in post neonatal period (62%). Birth asphyxia and pneumonia were major causes. The 1-5-year mortality rate was 1 per 1000 LB, which was only reported from the district of Chamba. There were zero maternal mortalities during the survey period. Conclusions & Recommendations: The IMR in tribal districts was higher than the state average. Most deaths were due to birth asphyxia, hence indicates the importance of labour room preparedness at PHCs in these hard-to-reach areas.